The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/cyt.12638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of the status of atypical endometrial cells using the descriptive reporting format for endometrial cytology

Abstract: ObjectiveWe aimed to develop and reinforce a clinical management regimen for atypical endometrial cell (ATEC) categories within the descriptive reporting format for endometrial cytology.MethodsBetween January 2013 and December 2014, 215 samples, for which histological examination was performed immediately or within 3 months after cytology, were cytologically diagnosed as ATEC. For these samples, the medical records were retrospectively reviewed to identify risk factors for malignancy.ResultsAmong 152 samples d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The new terminology for endometrial cytology has been introduced and now TYSEC system is usefully utilized. [1][2][3][4][5] However, diagnosis of gray zone category, ATEC, especially ATEC-US implies that clinicians would perform unnecessary biopsies. Accurate cytological diagnosis is required to maximize the merit of cytology, which seems less harmful than biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new terminology for endometrial cytology has been introduced and now TYSEC system is usefully utilized. [1][2][3][4][5] However, diagnosis of gray zone category, ATEC, especially ATEC-US implies that clinicians would perform unnecessary biopsies. Accurate cytological diagnosis is required to maximize the merit of cytology, which seems less harmful than biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that nearly 10% of the cases assigned to cytological ATEC-US category had corresponding malignant histology. [3][4][5] Although cytological gray zone category intrinsically has some amount of corresponding malignant histology, if it is large, it could cause a problem for managing patients with a cytological diagnosis of ATEC-US. Therefore, it would be ideal to minimize the number of cytological diagnosis of ATEC.…”
mentioning
confidence: 99%
“…21 However, several studies showed that increasing number of cases in gray zone category, especially ATEC-US in TYSEC, could cause problem in managing patients. [22][23][24] To solve the problem, a new approach to improve diagnostic accuracy have been expected. accuracy of endometrial carcinoma using thin-layer samples.…”
Section: Diagnostic Classification Of Endometrial Cytologymentioning
confidence: 99%
“…In order to improve diagnostic accuracy by standardization, sophisticated diagnostic algorithm by using LBC, the Osaki Study Group (OSG) method, was introduced as a reliable and reproducible method by a Japanese group 21 . However, several studies showed that increasing number of cases in gray zone category, especially ATEC‐US in TYSEC, could cause problem in managing patients 22–24 . To solve the problem, a new approach to improve diagnostic accuracy have been expected.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial cancer is one of the common gynecological malignancies that threaten women's health, 1,2 especially for women in the perimenopausal and postmenopausal period, 3 and the incidence rate has been on the rise in recent years. Atypical endometrial hyperplasia (AEH) is the precancerous lesion for EC, and its pathological morphological manifestation is similar to that of highly differentiated EC 4,5 . The co‐incidence rate for AEH and EC were 15–55%, 6 and they are similar in clinical treatments and surgical methods.…”
Section: Introductionmentioning
confidence: 99%